Comparative study of the properties of sericin-gelatin nanofibrous wound dressing containing halloysite nanotubes loaded with zinc and copper ions. Issue 18 (12th December 2019) - Massoumi, Hamed; Nourmohammadi, Jhamak; Marvi, Mehri Sadat; Moztarzadeh, Fathollah
Abstract: This study introduces and characterizes a novel antibacterial wound dressing from gelatin-sericin nanofibers containing halloysite nanotubes (HNTs) loaded with therapeutic copper and zinc ions. Finer fibers with faster bactericidal activity were observed in the Cu 2+ containing mat; however, the fibroblast viability was reduced in these samples. On the contrary, Zn +2 loaded nanofibers exhibited the best hosting area for fibroblast cells attachment, viability, and collagen secretion. Therefore, the proliferative effects of Zn-loaded gelatin-sericin nanofibers along with sufficient mechanical properties and favorable antibacterial activity proved that such a nanocomposite can have a potential of use as an antibacterial wound dressing. GRAPHICAL ABSTRACT: